Ginger Essential Oil Inhibits Biofilm Formation of Streptococcus mutans on Stainless Steel Placeholder - K, Alp Kayahan; K, Merih (Penerbit Universiti Kebangsaan Malaysia, 2023)
Streptococcus mutans (S. mutans) forms biofilm on dental apparatus and materials in the mouth as far as the tooth surface is concerned. This form of biofilm around the apparatus can cause decay in the teeth. In our study, the formation of biofilm on the stainless-steel space maintainer, which is frequently used in children, and its inhibition by ginger essential oil were examined. Minimum inhibitory concentration (MIC) assays for the antibacterial activities of the ginger essential oil was performed according to the microdilution broth method. The formation of the biofilm on the stainless steel space maintainer was evaluated spectrophotometrically and the number of bacteria in the biofilm was counted. Biofilm on stainless steel space maintainer was also examined with scanning electron microscopy (SEM). On the stainless steel space maintainer without ginger essential oil, S. mutans produced significant amounts of biofilm. Bacterial counts and SEM images also supported this finding. Ginger (Zingiber officinale) essential oil significantly inhibited the formation of biofilm and adhesion of S. mutans on the stainless-steel placeholder.